An embedded checklist in the Anesthesia Information Management System improves pre-anaesthetic induction setup: a randomised controlled trial in a simulation setting. Issue 10 (20th November 2015) - Wetmore, Douglas; Goldberg, Andrew; Gandhi, Nishant; Spivack, John; McCormick, Patrick; DeMaria, Samuel
Abstract : Background: Anaesthesiologists work in a high stress, high consequence environment in which missed steps in preparation may lead to medical errors and potential patient harm. The pre-anaesthetic induction period has been identified as a time in which medical errors can occur. The Anesthesia Patient Safety Foundation has developed a Pre-Anesthetic Induction Patient Safety (PIPS) checklist. We conducted this study to test the effectiveness of this checklist, when embedded in our institutional Anesthesia Information Management System (AIMS), on resident performance in a simulated environment. Methods: Using a randomised, controlled, observer-blinded design, we compared performance of anaesthesiology residents in a simulated operating room under production pressure using a checklist in completing a thorough pre-anaesthetic induction evaluation and setup with that of residents with no checklist. The checklist was embedded in the simulated operating room's electronic medical record. Results: Data for 38 anaesthesiology residents shows a statistically significant difference in performance in pre-anaesthetic setup and evaluation as scored by blinded raters (maximum score 22 points), with the checklist group performing better by 7.8 points (p<0.01). The effects of gender and year of residency on total score were not significant. Simulation duration (time to anaesthetic agent administration) was increased significantly by the use of the checklist. Conclusion: Required use of a pre-induction checklist improves anaesthesiology resident performance in a simulated environment. The PIPS checklist as an integrated part of a departmental AIMS warrant further investigation as a quality measure.